Improvements in patient‐reported outcomes in patients with psoriasis receiving etanercept plus topical therapies: results from REFINE. (21st January 2015) - Papp, K.A.; Barber, K.; Bissonnette, R.; Bourcier, M.; Lynde, C.W.; Poulin, Y.; Shelton, J.; Garces, K.; Toole, J.; Poulin‐Costello, M.
Abstract Background The REFINE study examined the efficacy and safety of adding topical corticosteroid therapy to etanercept when stepping down from the initial dose of etanercept to the maintenance dose. Clinical responses were shown to be similar in patients who remained on etanercept 50 mg twice weekly (BIW) and those who received etanercept 50 mg once weekly (QW) plus topical therapies through week 24. Objective The purpose of this analysis was to evaluate the effect of treatment on health‐related quality of life (HRQoL) for patients in REFINE. Methods All patients received etanercept 50 mg BIW for 12 weeks and were then randomized to etanercept 50 mg BIW or etanercept 50 mg QW plus topical corticosteroid as required to clear through week 24. HRQoL measures included the Dermatology Life Quality Index (DLQI), Treatment Satisfaction Questionnaire for Medication (TSQM) and the Economic Implications of Psoriasis Patient Questionnaire. No comparative testing was performed for this descriptive analysis. Missing data were imputed using the last observation carried forward. Results For 287 randomized patients (144 etanercept; 143 etanercept plus topical), the mean change [standard deviation (SD)] in DLQI from baseline to week 24 was 10.7 (7.8) for etanercept and 9.9 (6.9) for etanercept plus topical. Mean change (SD) in TSQM effectiveness, convenience, side‐effects and global satisfaction was 27.1 (36.1), 14.8 (25.9), −0.7 (22.0) and 26.7 (32.5) for the etanercept arm and 32.5 (40.3), 18.5 (29.0), 1.3 (19.4) and 28.4 (35.9) for etanercept plus topical. Economic implications, including healthcare visits, employment status, work productivity, ability to perform daily activities and out‐of‐pocket expenses were similar between treatment arms. Conclusion At week 24 of REFINE, measures of HRQoL were numerically similar in patients who stayed on etanercept 50 mg BIW and patients who received etanercept 50 mg QW plus topical therapies.